2008
DOI: 10.1186/1757-1626-1-357
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of advanced testicular seminoma in a 78-year-old man managed successfully with carboplatin based chemotherapy: a case report

Abstract: Background: Germ cell tumours are uncommon in aged man. We present a rare case of metastatic seminoma of the testis associated with liver and renal insufficiencies in a 78-years-old man managed successfully with carboplatin based chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Information is scarce in the available literature regarding the clinical outcome of older patients with malignant germ cell tumours in the era of platinum‐based chemotherapy, with just a few case reports of successful treatment [9–11]. A recent pathological review [2] of 50 germ cell tumours in the elderly (median age 67 years) found that most were seminomas (82% compared to the 73% reported in the series of the present study); however, complete information about staging or outcome was not given.…”
Section: Discussionmentioning
confidence: 68%
“…Information is scarce in the available literature regarding the clinical outcome of older patients with malignant germ cell tumours in the era of platinum‐based chemotherapy, with just a few case reports of successful treatment [9–11]. A recent pathological review [2] of 50 germ cell tumours in the elderly (median age 67 years) found that most were seminomas (82% compared to the 73% reported in the series of the present study); however, complete information about staging or outcome was not given.…”
Section: Discussionmentioning
confidence: 68%
“…Testicular seminoma accounts for 40%–60% of all testicular germ cell tumors, which are the most common solid tumors in males aged 15–35 years. 1 , 2 Although the cure rate of testicular seminoma at stage I (nonmetastasized seminoma) exceeds 95%, there is a poor prognosis once the tumor spreads to adjacent lymph node groups (including those in the neck, mediastinum, and abdomen), lung, liver, and bones. 2 6 Epidemiological studies have indicated that cryptorchidism, gonadal dysgenesis, familial testis cancer, and environmental exposure to chemical substances increase the risk of seminoma occurrence; however, the precise molecular pathogenesis of seminoma is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Because carboplatin does not require hydration during administration and produces fewer toxic adverse events than cisplatin, it is an optimal anticancer drug for patients who do not tolerate cisplatin. [1][2][3][4][5] Although carboplatin is considered safe and easy to use, it can induce cardiotoxicity via a mitochondrial-dependent apoptosis pathway, and a case of cardiac failure caused by carboplatin has been reported. 14,15 Thus, carboplatin should be carefully administered to patients with cardiac disease despite the fact that carboplatin-induced cardiac disease occurs at a low frequency.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship among the dose intensity, total number of cycles, and treatment outcome (including the rate of relapse) is very controversial. [4][5][6][7][8]16 Although there is no strict evidence for the efficacy of prolonged administration of carboplatin, including maintenance therapy, long-term carboplatin at 4 AUC may achieve therapeutic efficacy with minimal occurrence of serious adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation